Current status and the significance of local wisdom biofertilizer in enhancing soil health and crop productivity for sustainable agriculture: A systematic literature review - Irwandhi, Irwandhi; Khumairah, Fiqriah Hanum; Sofyan, Emma Trinurani; Kamaluddin, Nadia Nuraniya; Nurbaity, Anne; Herdiyantoro, Diyan; Simarmata, Tualar (Universitas Padjadjaran, 2024)
Soil fertility is recognized as a crucial factor in supporting plant growth and productivity. The utilization of biofertilizers as environmentally friendly fertilizers is aimed at enhancing soil fertility and plant productivity. This study aims to explore the potential of local material for developing local wisdom biofertilizers (LWB) for achieving sustainable agriculture. A systematic literature review was conducted using bibliometric analysis, Preferred Reporting Items for Systematic Reviews, and Meta-Analyses (PRISMA) method, employing the Scopus search engine with the keywords